JURIDIC REVIEW CONCERNING OBLIGATIONS TO PROVIDE FOOD SAFETY GUARANTEE BY BUSINESSES TO CONSUMERS BASED ON LAW NUMBER 18 YEAR 2012 CONCERNING CONSUMER PROTECTION - Sufmi Dasco Ahmad (Jurnal Multidisiplin Sahombu, 2021)
Food is the most important basic human need and its fulfillment is part of human rights guaranteed in the 1945 Constitution of the Republic of Indonesia. Food must always be safe. Food safety is a very important aspect in everyday life. Lack of attention to this, has often resulted in a detrimental impact on consumers. In relation to this food safety issue, Indonesia already has a legal basis that regulates it, namely Law Number 18 of 2012 concerning Food, and Law Number 8 of 1999 concerning Consumer Protection, which requires business actors to ensure food safety so as not to cause harm. for consumers. Based on this background, several problems are examined in this thesis, namely: 1. What is the obligation to provide food safety guarantees by business actors to consumers based on Law Number 18 of 2012 concerning Food in conjunction with Law Number 8 of 1999 concerning Consumer Protection ? and 2. What is the responsibility of business actors who do not provide food safety guarantees based on Law Number 18 of 2012 concerning Food in conjunction with Law Number 8 of 1999 concerning Consumer Protection? This research is a normative legal research, because it is conducted by examining secondary data, so that the research specification used is descriptive analytical, with a normative juridical approach, namely research conducted by examining secondary data. The secondary data was obtained by means of a literature study, then to draw conclusions from the research results, a qualitative juridical analysis was used. This study resulted in the following conclusions: 1. The obligation to provide food safety guarantees by business actors to consumers based on Law Number 18 of 2012 concerning Food in conjunction with Law Number 8 of 1999 concerning Consumer Protection has not been carried out optimally by business actors, so it has not been implemented optimally by business actors. sufficient to provide protection for consumers, due to the fact that there are still cases of food distribution that do not meet food safety standards, thereby harming consumers; and 2. Business actors who do not provide food safety guarantees based on Law Number 18 of 2012 in conjunction with Law Number 8 of 1999, are not only responsible for providing compensation for losses to consumers, but also may be subject to administrative sanctions and criminal sanctions. however, the sanctions as regulated in Law Number 18 of 2012, as well as Law Number 8 of 1999 in its implementation have not been fully implemented firmly, due to the fact that there are still cases of food distribution that do not meet food safety standards, thus harming consumers.